THE SIGNIGIFCANCE OF THE MEANS OF LITERARY EXPRESSIONS IN THE CHILDRENS GAME FOLKLORE OF THE OASIS OF SURKHAN - Sobirov Umid Bakhtiyorovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the following article the new ideas on the manifestation of the significance of the means of literary expressions in the children’s game folklore of the oasis of Surkhan is presented. The identical and differences are described based on the diverse sources of ethnical games, eposes and songs.